Understanding Consumer Receptiveness of Mortgage-Based Islamic Social Finance Using a Maqasid Framework: A Preliminary Study - Amin, Hanudin (Universitas Muhammadiyah Yogyakarta, 2019)
This study proposes a workable model of the mortgage-based Islamic social finance (MBISF) and to test the model acceptance using a maqasid framework empirically. Three battery items are intended to measure each latent variable. As for independent variables, the latent variables are an educational programme, mortgage welfare, consumer justice and Islamic debt policy, whilst as for a dependent variable, the latent variable is consumer receptiveness.Using Structural Equation Modelling (SEM) – Partial Least Squares or SEM-PLS, this study finds out that educational programme, mortgage welfare, consumer justice and Islamic debt policy are instrumental to lead the consumer receptiveness of MBISF. These results suggest that the elements of maqasid al-Shariah (education, welfare, justice and debt policy) are significant to consumer receptiveness of MBISF.The relationships established are then called as The Maqasid Theory of Consumer Behaviour (MTCB).Though the present work produced a fruitful outcome, yet the generalisation of the findings is somewhat limited and the application of the theory used in consumer behaviour is relatively fallen short or even unpopular in the conventional thinking. The results obtained provide better planning for Islamic banks to market their mortgages effectively.